Perbandingan Kadar Hemoglobin Pasca Transfusi Menggunakan Darah Segar dan Darah Simpan Pada Penderita Anemia Aplastik - Febria Ariandani; Meida Nugrahalia; Rahmiati Rahmiati (Universitas Medan Area, 2021)
This study aims to determine the comparison of hemoglobin levels in patients with aplastic anemia who are transfused using fresh blood and save blood in H. Adam Malik General Hospital Medan. This study was conducted descriptively by comparing the results of the increase in post-transfusion hemoglobin levels using fresh blood and save blood in patients with aplastic anemia. The results showed that the average value of hemoglobin in patients with aplastic anemia before being transfused with fresh donor blood was 6.4 gr/dL, increasing to 8.9 gr/dL, while the average value of hemoglobin levels in patients with aplastic anameia before transfusion of save blood is 6.8 gr/dL increased after transfusion to 7.9 gr/dL. It can be concluded that blood transfusion using fresh blood is better than storing blood transfusion in increasing hemoglobin levels in patients with aplastic anemia, with an average percentage increase in fresh blood of 38.0% and donor save blood an average of 17.4%.